Elastic stable intramedullary nailing for fractures in children – specific applications - Cosma, Dan; Vasilescu, Dana Elena (Medicine and Pharmacy Reports, 2014)
Elastic stable intramedullary nailing (ESIN) is a new minimally invasive technique for the treatment of pediatric fractures. It approximates the physiological healing process of bone, without opening the fracture site. Also, the operative stress is minimal because of the minimally invasive nature of the procedure, and the volume of implants is small, offering a very good stability without plaster cast immobilization.